Da'wah bi al-Hal within Islamic-Based Philanthropy: A Case Study of Darul Muhajirin Orphanage in Semarang - Qomariyah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2022)
This article attempts to discuss how the Islamic philanthropy of Darul Muhajirin orphanage in Semarang conducts da’wah bi al-hal (preaching by actual actions) towards the Muslim community living surrounding the orphanage and orphan children. Using a descriptive qualitative approach, the findings point out that da’wah bi al-hal conducted by Darul Muhajirin orphanage for community development and empowerment is an attempt to take part in community development efforts through social service activity programs. Hence, the existence of Darul Muhajirin orphanage is considered a benefit to the surrounding community. In regard to the method of da’wah bi al-hal, Darul Muhajirin orphanage has proposed several ways: first, exemplary in social movements like charity. Second, exemplary in worship; third, exemplary in the manner of speaking.